No Longer Religious, but Still Spending Money Religiously: Religious Rituals and Community Influence Consumer Behavior among Religious Dones - DeWall, C. Nathan (The international journal for the psychology of religion, 2022)
Many people spend money on religious and secular products. How do spending preferences change when people stop identifying as religious? People who stop identifying as religious (religious dones) may retain preferences for religious products more so than people who have never identified as religious (religious nones). Three studies (two preregistered; total N = 2,214) supported the religious residue hypothesis: currently religious participants expressed greater willingness to pay for religious products than did religious dones, who reported greater willingness to pay than did religious nones. Religious dones also expressed a greater desire to pay for secular products than for religious products, a pattern similar to religious nones. The religious residue effect was mediated by engagement in religious rituals and time spent with religious individuals.